Elevated Serum Level of Cytokeratin 18 M65ED Is an Independent Indicator of Cardiometabolic Disorders. (31st March 2020) - Qian, Lingling; Zhang, Lei; Wu, Liang; Zhang, Jing; Fang, Qichen; Hou, Xuhong; Gao, Qiongmei; Li, Huating; Jia, Weiping
Abstract : Background . Recent studies have suggested that cell death might be involved in the pathophysiology of metabolic disorders. The cytokeratin 18 (CK18) fragment, as a cell death marker, plays an important role in nonalcoholic fatty liver disease (NAFLD). However, only a limited number of studies have found elevated serum levels of CK18 in patients with type 2 diabetes. Moreover, no studies have been conducted yet to investigate the role of CK18 in hypertension or dyslipidemia. In particular, CK18 M65ED is a more sensitive marker of cell death, and its role in cardiometabolic disorders has not been revealed yet. Methods . A total of 588 subjects were enrolled from the local communities of Shanghai. Serum CK18 M65ED were determined using the enzyme-linked immunosorbent assay. A cardiometabolic disorder was identified by the presence of at least one of the components including overweight or central obesity, diabetes, dyslipidemia, and hypertension. Results . Subjects with cardiometabolic disorders exhibited significantly higher serum levels of CK18 M65ED than those without cardiometabolic disorders (197.36 (121.13–354.50) U/L versus 83.85 (52.80–153.75) U/L, respectively, P < 0.001 ). Increased serum CK18 M65ED quartiles were associated with the increased prevalence of cardiometabolic disorders and its components (P < 0.001 for all components). Multiple stepwise regression analysis also revealed that diastolic blood pressure, glycated hemoglobin A1c, alanine transaminase, and high-density lipoprotein cholesterol were independently correlated with serum CK18 M65ED levels (all P < 0.01 ). In addition, logistic regression analysis showed that the serum CK18 M65ED levels were positively correlated with cardiometabolic disorders and in an independent manner. Further, CK18 M65ED was revealed to be an indicator of cardiometabolic disorders in a NAFLD-independent manner. Conclusions . Elevated levels of CK18 M65ED, a sensitive cell death marker, were independently and positively correlated with cardiometabolic disorders, even after the adjustment for the presence of NAFLD and other cardiovascular risk factors.